Open, mixed, and moving: Recent Australian poetry. - Hart, Kevin (World Literature Today)
Discusses the evolution of Australian poetry. Traditional songs of the Aboriginal peoples; Seventeenth century coinage Terra Australis; Australia as terra nullius; Australian literature criticism as empirical; English as linguistically and culturally predominant; Historical markers as unreliable; Late 1960s as a time of loosening up and experimentation; `Em Malley' hoax; Continuing self concept; Australian poets and their works.